Strengthening Legal Awareness to Optimize the Implementation of the Complete Systematic Land Registration Program (PTSL) - Aan Risanah; Azhima Eka Putri (Jurnal Ilmu Hukum Kyadiren, 2026)
Land plays a strategic role in societal life; however, low levels of legal awareness among rural communities regarding the importance of land certification continue to impede the implementation of the Complete Systematic Land Registration Program (PTSL). This study aims to examine the stages of PTSL implementation, the interaction between formal and empirical law, the factors contributing to low legal awareness, as well as the obstacles and strategies associated with enhancing program effectiveness. The study employs an empirical juridical method with a socio-legal approach, utilizing interviews, observations, and document analysis as data collection techniques. The findings reveal that, although the implementation of PTSL generally conforms to existing legal provisions, its effectiveness remains limited due to low community participation, the predominance of empirical legal practices, and constraints in public outreach and administrative processes. The study concludes that the success of PTSL is closely linked to the integration of formal legal frameworks with prevailing social conditions, thereby necessitating participatory and educational strategies to strengthen legal awareness and improve program effectiveness.